Ottoman libraries : a survey of the history, development and organization of Ottoman foundation libraries = Osmanlı kütüphaneleri : Osmanlı vakıf kütüphanelerinin tarihi, gelişimi ve teşkilatı. - Erünsal, İsmail E. ([Harvard])
xxiv, 254 s.